Chemistry of the photoisomerization and thermal reset of nitro-spiropyran and merocyanine molecules on the channel of the MoS2 field effect transistor. Issue 48 (1st December 2021) - Mamun, Muhammad Shamim Al; Sainoo, Yasuyuki; Takaoka, Tsuyoshi; Waizumi, Hiroki; Wang, Zhipeng; Alam, Md Iftekharul; Ando, Atsushi; Arafune, Ryuichi; Komeda, Tadahiro
Abstract : The reversible reaction of the photoisomerization and thermal reset of photochromic spiropyrans and merocyanine deposited on the MoS2 FET channel. Abstract : We have explored the chemical reaction of the photoisomerization and thermal reaction of the photochromic spiropyran (SP) 1′, 3′-Dihydro-1′, 3′, 3′ trimethyl-6-nitrospiro[2H-1 benzopyran-2, 2′-(2H)-indole] molecule deposited on the atomic thin channel of a MoS2 field-effect transistor (FET) through the analysis of the FET property. With four monolayers of SP molecules on the channel, we observed a clear shift of the threshold voltage in the drain-current vs gate-voltage plot with UV-light injection on the molecule, which was due to the change of the SP molecule to merocyanine (MC). A complete reset from MC to SP molecule was achieved by thermal annealing, while the injection of green light could revert the FET property to the original condition. In the process of change from MC to SP, two types of decay rates were confirmed. The quick- and slow-decay components corresponded to the molecules attached directly to the substrate and those in the upper layer, respectively. The activation energies for the conversion of MC to SP molecules were estimated as 71 kJ/mol and 90 kJ/mol for the former and latter, respectively. Combined with DFT calculations, we concluded that the I d - V g shift with photoisomerization from SP to MC is due to the upper layer molecules and the dipole moment in the surface normal direction. Based on the estimated activation energy of 90 kJ/mol for the reset process, we calculated the conversion rate in a controllable temperature range. From these values, we consider that the chemical state of MC can be maintained and switched in a designated time period, which demonstrates the possibility of this system in logical operation applications.